Comparative perspectives on the archaeology of coastal South America - Cutright, Robyn E. (2010)
The bilingual conference from which the present volume emerged was conceived as a response to this situation, and was held in Lima, Peru in August of 2007. Conference participants were drawn from universities in Canada, Chile, Ecuador, Peru, Spain, and the United States to speak about their ongoing research along the Pacific coast of South America. By organizing sessions not by geographic zone but around common themes and questions, such as the mechanisms of state expansion or the emergence and maintenance of sociopolitical complexity, we hoped to facilitate a comparative approach to prehispanic coastal societies. We encouraged participants to emphasize not high theory or case-specific empirical details, but rather discuss concrete attempts to link research questions and methodology and place their work in broader comparative frameworks relevant to the coast. In addition to facilitating useful comparisons of diverse coastal cases and bringing to light fresh perspectives on the archaeology of the coast, we hoped that the conference would help build common ground for scholars working in different parts of the coast and contribute to lasting collaborative ventures between archaeologists working in Ecuador, Peru, and Chile. This volume contains eleven papers originally presented at the 2007 conference. In keeping with the original goals of the conference, papers are presented in both English and Spanish, and the volume is co-published by the University of Pittsburgh, the Pontificia Universidad Católica del Perú, and the Ministerio de Cultura del Ecuador.